Ask a New Question
Search
Questions and answers by
Kuai k
Answers (12)
z = (125-123)/(9.6/sqrt(144) z = 2/(9.6/12) z = 2.5 z-table 1-.0062 =0.9938
Not. It is wrong. -233-233 = -466
e^x /(3+3x) g'(x) = xe^x/(3(x+1)^2
4(1.65)/.13 6.60/.13 = $50.77
(4x+6)/(4x-6)(4x+6)/(2(x+7)(2x-3) = 1/(4x-6)/(2(x+7)(2x-3) = 1/(4(2x-3x)(2x^2+11x-21)
First not correct 4(1.65)/.13 6.60/.13 = $50.77
.13p = 1.65 .13p/.13 = 1.65/.13 P = 12.69
3x^5-1/4x^2 3(2)^5 -1/4(2)^2 3(32)-1/4(4) 3x^5-1/4x^2 3(-2)^5 -1/4(-2)^2 3(-32)-1/4(4)
(2x-6)-(3x-4)=-(-4+x)-4x+6 2x -6 -3x + 4 = 4 -x -4x +6 -x -2 = -5x + 10 -x +5x -2 = -5x +5x + 10 4x -2 =10 4x -2 + 2 = 10 + 2 4x = 12 4x/4 = 12/4 x = 3
1. A = lw w =4l-3 4l-3(l) = 297 4l^2 -3l = 297 4l^2 -3l - 297 =0 (4l+33)(l-9)= 0 l = 9 w =33 2. a^2 + b^2 = c^2 short leg = x Long leg = x+1 x^2 + (x+1)^2 = 7^2 x^2 +x^2 + x + x + 1 = 49 2x^2 +2x + 1 = 49 3. x, x +2 x (x+2) = 575 x^2+ 2x = 575 x^2 + 2x
This is a horizontal line, so a perpendicular line gives you a constant x value, providing the equation x=3
3x/4+5x/2=13 4(3x/4) + 4(5x/2) =4(13) 3x + 10x = 52 13x = 52 13x/13 = 52/13 x = 4